Macroeconomic Determinants of Tourism Demand Toward Emerging Markets - Burak Darıcı; Ahmet Aydın; Fatih Ayhan; Merve Altaylar (İstanbul İktisat Dergisi)
This research provides valuable insights into the intricate dynamics influencing tourism demand in Turkey. By delving into the relationships between transportation costs, tourists’ income levels, prices, the COVID-19 pandemic, and exchange rates, the study sheds light on the multifaceted nature of the tourism industry. The findings underscore the significance of various factors in shaping the tourism demand. Transportation costs and exchange rates are identified as critical determinants, exerting adverse effects on tourism demand. Higher transportation costs and unfavorable exchange rates can deter potential tourists However, income and prices emerged as positive influencers of tourism demand, suggesting that higher incomes and favorable price levels can stimulate tourist activity. The study’s investigation of causal relationships through advanced statistical techniques revealed valuable insights. The unidirectional causality from transportation costs and income to tourism demand highlighted the pivotal role of these factors in driving tourist behavior. Additionally, the causal relationship between prices and the exchange rate signifies the interplay between economic conditions and pricing strategies in shaping tourism demand. Overall, this research provides a deeper understanding of the complex dynamics in the Turkish tourism market, offering valuable insights for industry stakeholders and policymakers alike.